Консультування підприємств з організації і методики обліку для цілей оподаткування - Лакатош, Марія Ігорівна (Ірпінь, 2025)
У кваліфікаційній роботі розглядаються питання аналізу та обґрунтування теоретичних та методичних засад консультування підприємств з організації і методики обліку для цілей оподаткування. За результатами дослідження сформульовані практичні рекомендації щодо організації методики обліку для підвищення ефективності консультування підприємств. .

The qualification work deals with the analysis and substantiation of the theoretical and methodological foundations of consulting enterprises on the organisation and methodology of accounting for tax purposes. Based on the results of the study, practical recommendations on the organisation of accounting methods to improve the efficiency of consulting enterprises are formulated.
Advising companies on the organization and methodology of accounting for tax purposes
Keywords: консультування з питань оподаткування; податкове планування та оптимізація; податкове законодавство; tax consulting; tax planning and optimization; tax legislation